2021
DOI: 10.3389/fnmol.2021.678267
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose Consumption Alters Serotonin/Glutamate Co-localisation Within the Prefrontal Cortex and Hippocampus of Mice

Abstract: The overconsumption of sugar-sweetened food and beverages underpins the current rise in obesity rates. Sugar overconsumption induces maladaptive neuroplasticity to decrease dietary control. Although serotonin and glutamate co-localisation has been implicated in reward processing, it is still unknown how chronic sucrose consumption changes this transmission in regions associated with executive control over feeding—such as the prefrontal cortex (PFC) and dentate gyrus (DG) of the hippocampus. To address this, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 89 publications
(131 reference statements)
0
9
0
Order By: Relevance
“…4A–C ) and quantified (Fig. 4D–F ) as previously described [ 46 , 47 , 54 , 55 ]. The volume of 5-HT varicosities (boutons) in the DG, CA3 and LS was quantified in water-exposed animals (Water), ethanol-exposed animals chronically treated (2 weeks, following 12 weeks of consumption) with either vehicle (EtOH + veh) or with the 5-HT 1A receptor partial agonist, tandospirone at 3 mg/kg/day, i.p.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4A–C ) and quantified (Fig. 4D–F ) as previously described [ 46 , 47 , 54 , 55 ]. The volume of 5-HT varicosities (boutons) in the DG, CA3 and LS was quantified in water-exposed animals (Water), ethanol-exposed animals chronically treated (2 weeks, following 12 weeks of consumption) with either vehicle (EtOH + veh) or with the 5-HT 1A receptor partial agonist, tandospirone at 3 mg/kg/day, i.p.…”
Section: Resultsmentioning
confidence: 99%
“…Sections were rinsed in PBST (0.1 M PBS, 0.3% Triton-X100, 0.03% Tween-20), and incubated in Streptavidin-Alexa 488 (Thermofisher, S11223, 1:1000) diluted in PBST, at room temperature for 30 min, rinsed 3 × 5 min in PBST, incubated in DAPI diluted in PBS (Thermofisher, #D1306, 1:1000), rinsed 3 × 5 min in PBS and mounted on slide with Prolong Gold antifade (Thermofisher, #P10144). For 5-HT innervation, immunohistochemistry was performed by a blind experimenter as previously described [ 46 , 47 ]. Briefly, after permeabilization and blocking as above, sections were incubated with rat anti-5-HT antibody (Merck Millipore MAB352, 1:100) for 72 h at room temperature, followed by goat anti-rat biotinylated secondary antibody (Jackson Immunoresearch # 112-065-003, 1:200) for 4 h, and 30 min incubation with streptavidin-Cy3 (Thermofisher, #434315, 1:1000).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to sucrose, previous studies have demonstrated similarities following acute exposure to another non-caloric sweetener saccharin at the level of the NAc [ 134 , 135 , 136 ]. Very recent study indicated that chronic (12 weeks) 5% sucrose consumption to mice resulted in a reduction in the serotonin (5-HT) receptors innervation within the PFC and dentate gyrus of the hippocampus, a reduction in the number of microglia in the latter brain structure as well as a decrease in the density of the vesicular glutamate transporter (VGLUT3) and of 5-HT/VGUT3 varicosities but not in the number of oligodendrocyte progenitor cells [ 137 ].…”
Section: Hormonal and Neuronal Regulation Of Sugar Intakementioning
confidence: 99%
“…Hippocampus-dependent alteration in behaviours was accompanied with altered hippocampal neurogenesis such as a reduction in the proliferation and differentiation of newborn neurons in the dentate gyrus [ 141 ], which raises a positive correlation between high- and long-term exposure to sucrose during adolescent and neurocognitive defects in adulthood. Furthermore, anxiety-like or depressive-like symptoms being observed simultaneously following long-term 8–25% sucrose consumption [ 123 , 143 , 144 , 145 , 146 , 147 , 148 , 149 ], but not with 5% sucrose consumption [ 137 ]. In addition, a high sucrose intake (30% wt/vol) in pregnant mice induced behavioural phenotypes similar to ADHD in the offspring, manifested by increased motor activity, and impulsivity.…”
Section: Hormonal and Neuronal Regulation Of Sugar Intakementioning
confidence: 99%
“…In relation to emotions , changes in sucrose intake in rodents are known to reflect depressive-like behaviour [ 149 , 150 ]. In this respect, chronic sucrose consumption decreased the number of VGLUT3+ varicosities in the dentate gyrus of the mouse hippocampus independently from their 5-HT marker expression [ 151 ]. Interestingly, in rats, repeated sucrose consumption increased VGLUT3 expression in the nucleus accumbens, the centre known for reward, as well [ 152 ].…”
Section: The Hippocampusmentioning
confidence: 99%